HAWKING THERMAL RADIATION AND LIFETIME OF BLACK HOLES IN BRANEWORLD - Akhrorjon Mamajanov; O. R. Isoqova (Galaxy International Interdisciplinary Research Journal, 2022)
The thermodynamic properties of the primordial black hole, (PBH), in the braneworld are investigated. Hawking radiation and the life time of PBHs have been studied. An exact analytical expression for the Bekenstein-Hawking’s entropy, the temperature and heat capacity have been found. Time dependence of thermodynamic quantities of PBH has been studied. It is argued that the life time of PBHs in the early Universe is shortened at least for one order which lead to their evaporation. It can be a reason why we do not observe final rapid evaporation of PBHs in the recent epoch of the Universe.